Faith as a Therapeutic Companion: Instructing Counselling Students on the Import of Religion - Leighton, Trent (Canadian Journal of Counselling and Psychotherapy, 2016)
This article addresses the most efficacious means of teaching counselling students the import of religion when counselling faith-based clients. I present four fallacies that persist in counselling curricula: religious clients are hard to counsel, students must comprehend their clients’ religion before being able to comprehend clients’ therapeutic needs, existing courses cannot be used to deliver an effective religious education, and spiritual dialogue does not have a place in course content. Communicating a clinically salient religious understanding to students would enhance their curricular experience and therapeutic acumen, and can be taught concurrently within a counselling curriculum if faculty use existing programming.